2020
DOI: 10.1002/ange.202006149
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective CpxRhIII‐Catalyzed Carboaminations of Acrylates

Abstract: Enantioselective carboaminations of olefins constitute an attractive strategy for a rapid increase in molecular complexity from readily available starting materials. Reported here is an intermolecular asymmetric carboamination of acrylates using rhodium(III)-catalyzed alkenyl CÀH activations of N-enoxysuccinimides to generate the nitrogen and carbon portion for the transfer. A rhodium complex equipped with a tailored bulky trisubstituted chiral Cp x ligand ensures carboamination chemoselectivity as well high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…[59] Theg enerally accepted mechanism for the reaction is shown in Scheme 18 a. After in situ generation of the active Cp X Rh III catalyst 76,t he hydroxamate functionality coordinates to the metal center (77). Subsequently,acarboxylateassisted concerted metalation-deprotonation (CMD) takes place, [69] lyst.…”
Section: Rh III Catalysismentioning
confidence: 99%
“…[59] Theg enerally accepted mechanism for the reaction is shown in Scheme 18 a. After in situ generation of the active Cp X Rh III catalyst 76,t he hydroxamate functionality coordinates to the metal center (77). Subsequently,acarboxylateassisted concerted metalation-deprotonation (CMD) takes place, [69] lyst.…”
Section: Rh III Catalysismentioning
confidence: 99%
“…Alternatively,t he authors demonstrated later that by changing the catalyst from Mannitol-CpRh15 to BINOL-CpRh16,a nd running the reaction in methanol instead of trifluoroethanol, carboamination acyclic products 110 were generated instead. [77] Ab road range of unnatural a-amino acids (EWG = CO 2 R) were synthesized accordingly in moderate to high yields and with excellent enantioselectivity. Presumably,t he MeOH solvent assists by nucleophilic ringopening of the N-enoxysuccinimide substrate,being incorporated into the methyl ester products 110.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[59] Theg enerally accepted mechanism for the reaction is shown in Scheme 18 a. After in situ generation of the active Cp X Rh III catalyst 76,t he hydroxamate functionality coordinates to the metal center (77). Subsequently,acarboxylateassisted concerted metalation-deprotonation (CMD) takes place, [69]…”
Section: Rh III Catalysismentioning
confidence: 99%